Cystic artery pseudoaneurysm, a rare complication of duodenal ulcer - Nor Azizan, Aida Nadhirah; Ahmad, M. Ammar; Yu, Kah Ling (International Surgery Journal, 2023)
In this case report, we would like to discuss a rare case of cystic artery pseudoaneurysm. Multiple aetiology has been described in literatures. One of the rarest is duodenal ulceration causing erosion into the cystic artery, leading to pseudoaneurysm formation. Here, we presented a case of ruptured cystic artery pseudoaneurysm with duodenal ulcer presenting as lower gastrointestinal bleeding and its subsequent management.